1996
DOI: 10.1139/g96-107
|View full text |Cite
|
Sign up to set email alerts
|

Genome flux in tomato cell clones cultured in vitro in different physiological equilibria. II. A RAPD analysis of variability

Abstract: An analysis of the effect of changing physiological conditions on genome evolution in tomato cell populations has been carried out on long-term in vitro cultured clones grown on different auxin-cytokinin equilibria or selected for low-high competence for active defense against Fusarium oxysporum f.sp. lycopersici. RAPD analysis, confirmed through pattern rehybridization, was used as a random tool to measure the genetic variability. Through the use of a modified ANOVA, variation was shown to depend on both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…However, genetic analysis of such traits is often difficult, and their genetic causes remain unknown. Both methods reveal changes in the DNA nucleotide sequence and, in particular, neutral mutations [8][9][10][11]. We have previously observed that, although the ploidy changes in cultured pea cells, regenerated plants preserve the original ploidy, and phenotypic changes are not associated with considerable rearrangements of the karyotype [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, genetic analysis of such traits is often difficult, and their genetic causes remain unknown. Both methods reveal changes in the DNA nucleotide sequence and, in particular, neutral mutations [8][9][10][11]. We have previously observed that, although the ploidy changes in cultured pea cells, regenerated plants preserve the original ploidy, and phenotypic changes are not associated with considerable rearrangements of the karyotype [7].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that, at a specific cytokinin/auxin combinations, adventitious regeneration system can induce variability in blackberry Č ačanska Bestrna. There are also some reports suggesting that different levels of auxin/cytokinin can affect the rate of somaclonal variation in strawberry cultures (Nehra et al 1992) and tomato long-term culture (Bogani et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Somatic embryo plants have generally been less variable, and that indicated the maintenance of genetic fidelity; however, so-mac10nal variation could be observed when somatic embryo cultures were kept for a longer time in in-vitra conditions (Henry et al, 1997). Bogani et al (1995Bogani et al ( , 1996 analysed genetic variation with RAPDs in tomato long-term cultures grown on media containing different auxinlcytokynin equilibria. Thus, subcloning in Haworthia (Ogihara, 1990), an increase in the number of propagation cycles in Begonia (Westerhof et al, 1984), and ageing of Begonia (CasseIls and Morrish, 1987) and Pelargonium cultures , all increased chromosomal and/or phenotypic variation among regenerated plants (Table 8).…”
Section: Frequency Modulation Of Somaclonal Variabilitymentioning
confidence: 99%